2017
DOI: 10.1002/jbm.b.33963
|View full text |Cite
|
Sign up to set email alerts
|

Osteoinductive porous biphasic calcium phosphate ceramic as an alternative to autogenous bone grafting in the treatment of mandibular bone critical‐size defects

Abstract: The bone-induction capacity of a porous biphasic calcium phosphate (pBCP) using heterotopic implantation in mouse (mHI-model) and its efficacy as substitute for autograft in mandibular critical-size defect in rabbit (rabMCSD-model) was investigated. In mHI-model, pBCP was implanted into the thigh muscles and bone formation was histomorphometrically and immunohistochemically evaluated. In rabMCSD-model, 13 mm bone defects were treated with pBCP or autograft and bone repair comparatively evaluated by radiographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 43 publications
1
28
1
3
Order By: Relevance
“…37 The most commonly used calcium phosphate ceramics are HA and -TCP at various weight ratios. 41,42 The high biocompatibility, increase safety, high predictability, unlimited availability, low morbidity for patients, and cost-effectiveness of calcium phosphate ceramics all represent important advantages over autografts and allografts. 41,42 The high biocompatibility, increase safety, high predictability, unlimited availability, low morbidity for patients, and cost-effectiveness of calcium phosphate ceramics all represent important advantages over autografts and allografts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 The most commonly used calcium phosphate ceramics are HA and -TCP at various weight ratios. 41,42 The high biocompatibility, increase safety, high predictability, unlimited availability, low morbidity for patients, and cost-effectiveness of calcium phosphate ceramics all represent important advantages over autografts and allografts. 41,42 The high biocompatibility, increase safety, high predictability, unlimited availability, low morbidity for patients, and cost-effectiveness of calcium phosphate ceramics all represent important advantages over autografts and allografts.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40] Calcium phosphate ceramics have shown bioactivity and osteoconductivity in previous papers. 41,42 The high biocompatibility, increase safety, high predictability, unlimited availability, low morbidity for patients, and cost-effectiveness of calcium phosphate ceramics all represent important advantages over autografts and allografts. 43 Although the ideal ratio of HA to -TCP is still under investigation, [44][45][46] variant ratios of BCPs have been widely used for bone graft substitutes, with favorable results A review of the commercially available BCP indicated that the most common ratio is 60% HA and 40% -TCP.…”
Section: Discussionmentioning
confidence: 99%
“…The biomaterials used for scaffold preparation are natural biopolymers, synthetic polymers, ceramics and composites [ 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. Natural biopolymers include chitosan [ 28 , 60 , 61 , 62 , 63 ], alginate [ 46 , 64 , 65 ], cellulose [ 66 , 67 , 68 ], collagen [ 33 , 35 , 69 ], hyaluronan [ 70 , 71 , 72 ], fibrin [ 73 , 74 , 75 , 76 ] and silk [ 77 , 78 ].…”
Section: Biomaterials For Scaffold Fabricationmentioning
confidence: 99%
“…Thus, bone formation occurred around the BCP granule surfaces locally, but in a panoramic view, the bone was formed from the border toward the center of the defects and also from the duramater side toward the teguments (figure 5, 12 st article). A previous study from our research group analyzed HA/TCP 70/30 implanted in mandibular critical size defects and within muscle bundles and reported new bone formation over their surface, pores and concavities (Santos et al, 2018). While comparing granules size of this BCP, different microenvironments were stablished that may explain the differences in bone formation rate among the granular size groups.…”
Section: Discussionmentioning
confidence: 95%